Biomarkers of damage and protection in Mytilus galloprovincialis cross transplanted in Ria Formosa Lagoon (Portugal) - Maria, Vera L. (2020)
The study was carried out to check the water contamination in two sites of Ria Formosa Lagoon by assessing the damage responses versus protection in the gills and digestive gland (Dg) of mussels--Mytilus galloprovincialis Lmk. Damage was assessed as DNA integrity and lipid peroxidation (LPO) while protection was evaluated by measuring catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GR), glutathione S-transferase (GST), total glutathione (GSHt) and metallothioneins (MT). Mussels were collected in March of 2007 at Ramalhete (R) as a reference site and Faro port (F) as harbour area. Cross transplantation was from R to F and vice versa performed during 0, 3 and 6 days. Gills DNA integrity decrease was observed in mussels transplanted to F (3 days) and R (6 days). Highest Dg LPO was found in mussels sampled at R. Elevated gills CAT, GPx, GR and GST was observed in mussels transplanted to F. Dg GSHt decreased in mussels transplanted to F. Gills and Dg mussels MT increased in mussels transplanted to R. M. galloprovincialis responses show their capability as early warning signals of the contaminants presence. The adopted approach, considering simultaneously protection responses and damaging effects, also revealed its usefulness on the pollution assessment.